2014
DOI: 10.1007/s00264-014-2551-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of multiple drilling on a sclerotic proximal tibia during total knee arthroplasty

Abstract: Purpose To assess the depth of cement penetration and the occurrence of radiolucent line (RLL) according to drill bit diameter used in multiple drilling for the sclerotic bone of the medial proximal tibia during total knee arthroplasty (TKA). Methods The multiple drilling procedure was performed with 2.0 mm diameter in group 1 (n=290) and with 4.5 mm diameter in group 2 (n=109) to enhance the cement penetration. The postoperative RLL in the cement-bone interface and the depth of cement penetration were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Only 1 of the studies compared different diameter of drilling holes and concluded that 4.5 mm diameter holes were superior to 2.0 mm holes in a sclerotic medial tibial plateau (Ahn et al. 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Only 1 of the studies compared different diameter of drilling holes and concluded that 4.5 mm diameter holes were superior to 2.0 mm holes in a sclerotic medial tibial plateau (Ahn et al. 2015).…”
Section: Resultsmentioning
confidence: 99%
“…This has also been demonstrated in both cadaveric and clinical studies which have shown improved cement penetration depth, better bone-cement interface strength, and significantly better pull-out force when pulsed lavage was used. [20][21][22] Drilling sclerotic bone has been shown to increase cement penetration on postoperative radiographs in clinical studies as well as improving pull-out strength in cadaveric studies, 23,24 but as yet, there are no clinical studies showing that this improves implant survivorship. The heterogenous nature of TKA failure means such a study may be difficult or impossible.…”
Section: Discussionmentioning
confidence: 99%
“…Drilling sclerotic bone has been shown to increase cement penetration on postoperative radiographs in clinical studies as well as improving pull-out strength in cadaveric studies, 23 , 24 but as yet, there are no clinical studies showing that this improves implant survivorship. The heterogenous nature of TKA failure means such a study may be difficult or impossible.…”
Section: Discussionmentioning
confidence: 99%
“…8,19 25 As implant design and polyethylene production have improved, we have seen a decline in failure due to polyethylene wear and subsequent osteolysis. 26,27 As such, other factors of implant fixation that have gained recent scrutiny and include factors related to the cement or implant include: (1) implant selection with considerations for surface roughness, 28 implant material, 28,29 implant pattern, 28 and placement; 24,30 (2) surface preparation including perforation of sclerotic bone 3,31 and pulsed lavage 32 34 ; (3) viscosity of the cement 6,11,35 ; and (4) cementation technique 4,7,9,34,36 to include the set phase, 9 penetration, and coverage 7,36 (surface, bisurface, or fully cemented keels). The recognition that cementation technique is a potential contributing factor to aseptic loosening may be of importance, particularly if there is a lack of consensus on best practice, standardization in technique, and documentation thereof.…”
Section: Discussionmentioning
confidence: 99%
“…3 Perforation of the sclerotic bone has been shown to improve cement penetration and decrease radiolucent lines at 1- and 2-year follow-up when larger diameter (4.5 mm) bits are used. 31 Final preparation of the bone–cement interface is best performed using pulsed lavage. In separate studies, Schlegel et al 32,33 confirmed the importance of bone preparation and pulsed lavage in enhancing fixation strength and recommended that it is a mandatory step in surface preparation along with copious drying of the tibial surface when cementing tibial components in TKA.…”
Section: Discussionmentioning
confidence: 99%